2021
DOI: 10.1002/joc.7270
|View full text |Cite
|
Sign up to set email alerts
|

The thermal state of the North Atlantic and macro‐circulation conditions in the Atlantic‐European sector, and changes in sunshine duration in Central Europe

Abstract: This article explains the reasons for the long-term variability in sunshine duration (SD) in Central Europe. It presents a recently discovered mechanism regulating changes in sunshine duration, not described so far in the literature. The periods of global dimming and global brightening were linked with changes in the annual frequency of the macrotypes of the middle-tropospheric circulation and the variability in the surface component of the thermohaline circulation in the North Atlantic (NA THC). On the basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 54 publications
2
18
0
1
Order By: Relevance
“…In Poland, as well as elsewhere in Europe, increasing trends in sunshine duration (e.g. Norris & Wild, 2007;Sanchez-Lorenzo, 2015;Bartoszek et al, 2021;Marsz et al, 2022) and in air temperature (e.g. Hoy et al, 2016;Sippel et al, 2016;Ustrnul et al, 2021;Kejna & Rudzki, 2021) have been observed in the last 40 years.…”
Section: Discussion Of the Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In Poland, as well as elsewhere in Europe, increasing trends in sunshine duration (e.g. Norris & Wild, 2007;Sanchez-Lorenzo, 2015;Bartoszek et al, 2021;Marsz et al, 2022) and in air temperature (e.g. Hoy et al, 2016;Sippel et al, 2016;Ustrnul et al, 2021;Kejna & Rudzki, 2021) have been observed in the last 40 years.…”
Section: Discussion Of the Resultsmentioning
confidence: 98%
“…Yet another view is presented by Sutton and Dong (2012) as well as Marsz and Styszyńska (2019), who claim that the increase in sunshine duration and warming in Europe is largely determined by changes in the thermal state of the World Ocean Waters (von Schuckmann et al, 2020). Moreover, Marsz et al (2022) suggested that long-term variability in sunshine duration over Central Europe was due to changes in the annual frequency of macrotypes of the middle-tropospheric circulation and the variability in the surface component of the thermohaline circulation in the North Atlantic (NA THC). The influence of atmospheric circulation on changes in spatial variability of air temperature in Poland was shown, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Цікаві зміни багаторічної мінливості ТСС відзначаються у центральній і східній Європі. Так, у статті A. Andrzej [14] показано зміну знаку багаторічного тренду цієї величини, зі зменшення до зростання, з середини 1990 -х рр.…”
Section: опис і аналіз результатівunclassified
“…Since an increase in SD is the cause of an increase in temperature, the question is what process led to the change in SD. Research by Marsz et al (2022) showed that changes in the intensity of the North Atlantic thermohaline circulation (NA THC) controlled changes in solar radiation in Central europe by regulating the course of the processes of the middle and lower circulation. The intensity of NA THC is characterised by the index defined by the acronym DG 3L .…”
Section: Sd the Mid-tropospheric Circulation And The Thermal State Of...mentioning
confidence: 99%